Development of a Novel Anti-CD19 CAR Containing a Fully Human scFv and Three Costimulatory Domains - Wutti-in, Yupanun; Sujjitjoon, Jatuporn; Sawasdee, Nunghathai; Panya, Aussara; Kongkla, Katesara; Yuti, Pornpimon; Yongpitakwattana, Petlada; Thepmalee, Chutamas; Junking, Mutita; Chieochansin, Thaweesak; Poungvarin, Naravat; Yamabhai, Montarop; et al. (Frontiers in Oncology, 2022)
Second-generation anti-CD19-chimeric antigen receptor T cells (anti-CD19-CAR2 T cells) are effective for treating B-cell malignancies; however, anti-CD19-CAR2 T cells can induce human anti-mouse immune responses because anti-CD19 single-chain variable fragment (scFv) in the CAR molecules is derived from a murine FMC63 (mFMC63) monoclonal antibody. Consequently, the persistence of mFMC63-CAR2 T cells and their therapeutic efficiency in patients are decreased, which results in tumor relapse. In an attempt to remedy this shortcoming, we generated a new anti-CD19-CAR T cells containing fully human anti-CD19 scFv (Hu1E7-CAR4 T cells) to pre-clinically evaluate and compare with mFMC63-CAR4 T cells. The human anti-CD19 scFv (Hu1E7) was isolated from a human scFv phage display library and fused to the hinge region of CD8α, the transmembrane domain of CD28, three intracellular costimulatory domains (CD28, 4-1BB, and CD27), and a CD3ζ signaling domain (28BB27ζ). Compared to mFMC63-CAR2 T cells (BBζ) and mFMC63-CAR3 (BB27ζ), the mFMC63-CAR4 T cells (28BB27ζ) exerted superior anti-tumor activity against Raji (CD19+) target cell. The Hu1E7-CAR4 and mFMC63-CAR4 T cells demonstrated comparable cytotoxicity and proliferation. Interestingly, compared to mFMC63-CAR4 T cells, the Hu1E7-CAR4 T cells secreted lower levels of cytokines (IFN-γ and TNF-α), which may be due to the lower binding affinity of Hu1E7-CAR4 T cells. These findings demonstrated the successfulness in creation of a new CAR T cells containing a novel fully human-derived scFv specific to CD19+ cancer cells. In vivo studies are needed to further compare the anti-tumor efficacy and safety of Hu1E7-CAR4 T cells and mFMC63-CAR4 T cells.